RNA‐seq profiling reveals different pathways between remodeled vessels and myocardium in hypertrophic cardiomyopathy. (14th October 2022) - Pisano, Annalinda; Pera, Loredana Le; Carletti, Raffaella; Cerbelli, Bruna; Pignataro, Maria G.; Pernazza, Angelina; Ferre, Fabrizio; Lombardi, Maria; Lazzeroni, Davide; Olivotto, Iacopo; Rimoldi, Ornella E.; Foglieni, Chiara; et al.
Abstract: Objective: Coronary microvascular dysfunction (CMD) is a key pathophysiological feature of hypertrophic cardiomyopathy (HCM), contributing to myocardial ischemia and representing a critical determinant of patients' adverse outcome. The molecular mechanisms underlying the morphological and functional changes of CMD are still unknown. Aim of this study was to obtain insights on the molecular pathways associated with microvessel remodeling in HCM. Methods: Interventricular septum myectomies from patients with obstructive HCM ( n  = 20) and donors' hearts (CTRL, discarded for technical reasons, n  = 7) were collected. Remodeled intramyocardial arterioles and cardiomyocytes were microdissected by laser capture and next‐generation sequencing was used to delineate the transcriptome profile. Results: We identified 720 exclusive differentially expressed genes (DEGs) in cardiomyocytes and 1315 exclusive DEGs in remodeled arterioles of HCM. Performing gene ontology and pathway enrichment analyses, we identified selectively altered pathways between remodeled arterioles and cardiomyocytes in HCM patients and controls. Conclusions: We demonstrate the existence of distinctive pathways between remodeled arterioles and cardiomyocytes in HCM patients and controls at the transcriptome level.